Inhibitor a-glucosidase activity of Pediococcus acidilactici DNH16 isolated from Dali ni Horbo, a traditional food from North Sumatra, Indonesia - EDY FACHRIAL; SARI ANGGRAINI; HARMILENI HARMILENI; SARYONO SARYONO; TITANIA T. NUGROHO (Society for Indonesian Biodiversity, 2023)
Abstract. Fachrial E, Anggraini S, Harmileni, Saryono, Nugroho TT. 2023. Inhibitor a-glucosidase activity of Pediococcus acidilactici DNH16 isolated from Dali ni Hhorbo, a traditional food from North Sumatra, Indonesia. Biodiversitas 24: 958-965. Traditional foods, specifically those made from milk, are a potential source of probiotics. These components positively impact digestion and inhibit ?-glucosidase, implying that they can be used as supplements for type 2 diabetes patients. Therefore, this study aims to isolate and identify probiotics from Dali ni Horbo, which have a-glucosidase inhibitory activity. Lactic Acid Bacteria (LAB) isolates from Dali ni Horbo were characterized morphologically and biochemically using Gram staining, Catalase test, and type of fermentation. They were further analyzed for their probiotic properties, namely antimicrobial activity, using agar diffusion, acid resistance, and bile salt with a spectrophotometer. Isolates that showed the highest antimicrobial activity, acid resistance, and bile salt were then further analyzed for their ?-glucosidase inhibitor activity. The samples were then identified molecularly using PCR amplifying the 16S rRNA gene. The PCR products were sequenced and submitted to the NCBI GenBank to determine the homology of the microorganism. The results showed that 1 out of 23 isolates, namely DNH16, had the highest antimicrobial activity against Staphylococcus aureus with an inhibition zone of 4.6 mm. It also has a high tolerance to acidic environments and bile salt, indicated by the percentage growth of 91.6% and 66.5% in an MRS medium containing 0.3% bile salt with a pH of 3. DNH16 isolate showed a-glucosidase inhibitor activity of 27% and was identified as Pediococcus acidilactici. The results show DNH16 has the potential to be used as a probiotic as well as an a-glucosidase inhibitor.